Improving Spectral Efficiency in Space Communications using SRRC Pulse-Shaping Technique - Simon Wasinya, Pallam; Hikma, Shabani; Dayang Azra, Awang Mat; Norhuzaimin, Julai (UTEM, 2017)
This paper proposes an improved spectral efficiency in space communications using square root raised cosine (SRRC) pulse-shaping technique. The proposal is necessitated by the global shortage of bandwidths confronting the wireless communication system. The major contribution of this technique is its ability to reduce the channel bandwidth and eliminate inter-symbol interference and spectral seepages with ease. This is achieved by tightly constraining wider channel bandwidths in a given frequency spectrum using SRRC pulse-shape filtering, thus eliciting more channels, higher data rates per channel and more users in the system. To authenticate the rationality of the proposed technique, MATLAB simulations are carried out under varying SRRC filter roll-off factors. The proposed technique is capable of achieving 43.76% channel bandwidth improvement, which is close to an ideal case of 50%. This is a great achievement in band-limited communication system. It is envisioned that this technique will be very helpful to designers of high performing and bandwidth efficient space communication system.